Low Hemoglobin among Pregnant Women in Midwives Practice of Primary Health Care, Jatinangor, Indonesia: Iron Deficiency Anemia or β-Thalassemia Trait? - Ari Indra Susanti; Edhyana Sahiratmadja; Gatot Winarno; Adhi Kristianto Sugianli; Herman Susanto; Ramdan Panigoro (Anemia)
Low hemoglobin (Hb) or anemia is common among pregnant women in developing countries which may cause adverse pregnancy outcomes and maternal deaths. Our study aimed to assess Hb level measured by midwives in primary health care facility at rural area of Jatinangor, Indonesia, and to explore whether the anemia was due to iron deficiency (IDA) or β-thalassemia trait (β-TT). Pregnant women (n=105) had finger prick test for Hb level during a regular antenatal care examination from October to November 2016. Hb level by finger prick test was compared with venous blood, measured by complete blood count (CBC). Indices including MCV and MCH and indices of Shine & Lal, Mentzer, Srivastava, Engels & Frase, Ehsani, and Sirdah were analyzed to differentiate anemia due to IDA and anemia due to suspect β-TT. HbA2 was measured to confirm β-TT. Anemic pregnant women were found in 86.7% by finger prick test compared to 21.9% (n=23) by CBC. The prevalence of β-TT in our study was 5.7%. Hb measurement among pregnant women in low resource area is highly important; however, finger prick test in this study showed a high frequency of anemia which may lead to iron oversupplementation. A standard CBC is encouraged; MCV and MCH would help midwives to identify β-TT.